Coexistence of a metastable double hcp phase in bcc–fcc structure transition of Te under high pressure. (19th January 2018) - Akahama, Yuichi; Okawa, Naoki; Sugimoto, Toshiyuki; Fujihisa, Hiroshi; Hirao, Naoshisa; Ohishi, Yasuo
Abstract: The structural phase transitions of tellurium (Te) are investigated at pressures of up to 330 GPa at 298 K using an X-ray powder diffraction technique. In the experiments, it was found that the high-pressure bcc phase (Te-V) transitioned to the fcc phase (Te-VI) at 99 GPa, although a double hcp phase (dhcp) coexisted with the fcc phase. As the pressure was increased and decreased, the dhcp phase vanished at 255 and 100 GPa, respectively. These results suggest that the dhcp phase is metastable at 298 K and the structure of the highest-pressure phase of Te is fcc. The present results provide important information regarding the high-pressure behavior of group-16 elements.